The story of Congress House, 1958 (page 1) (1958)
1958 1945-1960 "The story of Congress House, 1958 (page 1)" [T0349.jpg], 1958, Trades Union Congress In 1948 David du Roi Aberdeen won an architectural competition to design the new TUC headquarters building in Great Russell Street, London. Staff began to move into the offices in 1956 and the building was officially opened in 1958. The building is Grade II* listed.